Regulated protein kinases and phosphatases in cell cycle decisions. - Novak, B; Kapuy, O; Domingo-Sananes, MR; Tyson, J (2010)
Many aspects of cell physiology are controlled by protein kinases and phosphatases, which together determine the phosphorylation state of targeted substrates. Some of these target proteins are themselves kinases or phosphatases or other components of a regulatory network characterized by feedback and feed-forward loops. In this review we describe some common regulatory motifs involving kinases, phosphatases, and their substrates, focusing particularly on bistable switches involved in cellular decision processes. These general principles are applied to cell cycle transitions, with special emphasis on the roles of regulated phosphatases in orchestrating progression from one phase to the next of the DNA replication-division cycle.